Investigating the Relationship between Nursing Technicians’ Clinical Practicum Satisfaction, Preceptor Support, and Intention to Stay in the Profession: A Cross-Sectional Survey Study - Wardah Turki Jamaan Aldhafeeri; Manal Naif M Alrawili; Jawaher Dali Hudayris Alshammari; Maali Rahil Huran Alruwaili; Munairah Atwan S Alshammari; Afrah Bader Dakhel Alshammar (International Journal of Medical Toxicology and Legal Medicine, 2024)
Objective: This cross-sectional survey study aimed to investigate the relationships between nursing technicians’ satisfaction with their clinical practicum, perceived preceptor support, and intention to stay in the nursing profession. Methods: A sample of 450 nursing technicians completed validated questionnaires assessing clinical practicum satisfaction, preceptor support, and intention to stay. Descriptive statistics, Pearson correlations, and multiple regression analysis were performed. Results: Nursing technicians reported moderate levels of clinical practicum satisfaction (M=3.62, SD=0.81), preceptor support (M=3.51, SD=0.92), and intention to stay (M=3.24, SD=1.06). Clinical practicum satisfaction (r=0.39, p<0.001) and preceptor support (r=0.35, p<0.001) were positively correlated with intention to stay. In the regression model, clinical practicum satisfaction (β=0.27, p<0.001) and preceptor support (β=0.22, p<0.001) significantly predicted intention to stay, explaining 21% of the variance. Conclusions: Enhancing nursing technicians’ clinical practicum experiences and providing strong preceptor support may increase their job satisfaction and retention. Strategies to optimize the clinical learning environment and preceptorship programs are recommended.